2018
DOI: 10.1021/acs.chemmater.7b05316
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Electronic Structure near the Energy Gap of Graphitic Carbon Nitride Based on Rational Interpretation of Chemical Analysis

Abstract: Graphitic carbon nitride (g-CN) has attracted enormous interest in applications as a visible-light-driven photocatalyst, particularly for hydrogen evolution via water splitting. Despite intensive photocatalytic works to achieve higher hydrogen-evolution rate, the chemical and electronic structures that are essential for the water photolysis reactions have not been comprehensibly understood. To reveal the fundamental properties, we utilized well-oriented g-CN films for reliable analyses with several types of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
100
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 59 publications
18
100
1
1
Order By: Relevance
“…The C/N ratio is lower than the theoretical values of 0.75, however it is consistent with literature data [9,45,46]. Akaike et al [42] have reported C/N = 0.67, which corresponds to the composition of melon. Miller et al, [45] using annealing at 600 • C have obtained samples of C/N = 0.67.…”
Section: Elemental Analysissupporting
confidence: 90%
See 1 more Smart Citation
“…The C/N ratio is lower than the theoretical values of 0.75, however it is consistent with literature data [9,45,46]. Akaike et al [42] have reported C/N = 0.67, which corresponds to the composition of melon. Miller et al, [45] using annealing at 600 • C have obtained samples of C/N = 0.67.…”
Section: Elemental Analysissupporting
confidence: 90%
“…Powder X-ray diffraction patterns of carbon nitride samples obtained from different precursors in different conditions of annealing are shown in Figure 4. Thanks to the graphitic-like structure of carbon nitride it is possible to observe the reflections from the (002) crystal plane at ~27.7° 2θ which is related to the interlayer stacking of aromatic rings, and from the plane at ~13.3° 2θ ( Figure 4) which is related to the in-plane structural packing motif of tri-s-triazine units in melon (separation between parallel melon chains) [39][40][41][42]. At first sight, the differences between diffractograms of the g-C3N4 samples obtained in different conditions and from different precursors are slight.…”
Section: Morphological Characterizations (Xrd and Sem)mentioning
confidence: 99%
“…The deconvolution of the N1s peak shows the typical heptazinic conjugated nitrogen groups and terminal amino groups at 401.3 eV (Figure g). With respect to the conjugated nitrogen atoms, the central heptazinic nitrogen component is found at 400.1 eV, while the intense N‐aromatic nitrogen peak appears at 398.2 eV . The chemical structure of the herein presented pCN thin films is in good agreement with previous reports on pCN and is further confirmed by FTIR spectroscopy (Figure S7, Supporting Information).…”
supporting
confidence: 89%
“…The highly intense peak at 288.3 eV is attributed to sp 2 carbon of the heptazine rings (NCN), whereas the one at 286.4 eV typical for carbon bound to amino terminal groups is very low . The peak at 284.6 eV is attributed to CC bonds from adventitious carbon, usually unintentionally adsorbed on the pCN thin film surface . The deconvolution of the N1s peak shows the typical heptazinic conjugated nitrogen groups and terminal amino groups at 401.3 eV (Figure g).…”
mentioning
confidence: 98%
See 1 more Smart Citation